2002
DOI: 10.1002/1521-4001(200208)82:8<507::aid-zamm507>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Creep Analysis of Thin-Walled Structures

Abstract: Ingenieurwerkstoffe neigen bei erhöhten Temperaturen zusätzlich zum elastischen Verhalten zum Kriechen oder, mit anderen Worten, man kann neben einer spontanen Werkstoffreaktion auch eine zeitabhängige beobachten. Unter Berücksichtigung der wachsenden Sicherheitsanforderungen für Kraftwerke, Flugzeugkomponenten, chemischen Anlagen usw. ist das zeitabhängige Werkstoffverhalten in den Konstruktionsprozess einzubeziehen. Zahlreiche Bauteile, die unter Kriechbedingungen eingesetzt werden, können als dünnwandig kla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…where 0 is a regular hydrostatic constant not going to infinity if ℎ → 0 unlike 0 in (9). The presence of the sign function confirms the irregularity of the solution (1.11), (1.12) near the middle section 1 = 0 and its validity only at a distance from this section.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…where 0 is a regular hydrostatic constant not going to infinity if ℎ → 0 unlike 0 in (9). The presence of the sign function confirms the irregularity of the solution (1.11), (1.12) near the middle section 1 = 0 and its validity only at a distance from this section.…”
mentioning
confidence: 52%
“…compliant with the Equations (4), (6) by taking (9) as well as with the kinematic conditions (7) into account. In many aspects the "analytical history" of the Prandtl problem begins with the formulae (9) and (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The function 1 (t, w) given by (13), as |w| → ∞, the same property as the function F 1 (t, w) has. By the inverse transformation of equality (13) and using the generalized Parseval's formula we obtain…”
Section: Solution Of the Integro-differential Equation (2)mentioning
confidence: 82%
“…The contact problems of tension and bending of plates with inclusion of variable rigidity are investigated in [5][6][7]. The complete study of various possible forms of viscoelastic relations is given in the book [8], some aspects of the general theory of viscoelasticity are studied in [9,10], the research in the field of material's creep can be found in [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%